Influence of rigor mortis on tendon mobility in an animal fresh cadaver model - Lücke, Christoph; Schnetzke, Marc; Weiß, Christel; Studier-Fischer, Stefan; Gühring, Thorsten; Grützner, Paul Alfred; Porschke, Felix (Biology, 2022)
(1) Many biomechanical studies are performed using fresh frozen cadavers or embalmed specimens, although the biomechanical characteristics do not match the characteristics of in vivo tendons. Therefore, a fresh in vivo-like cadaver model has been introduced recently. As a limitation for studies with fresh cadavers, rigor mortis must be considered. The aim of this study was to evaluate the impact of the biomechanical properties and time of occurrence of rigor mortis in a fresh cadaver model. (2) For this study, 15 fresh porcine cadaver shoulders were used in an established biomechanical in vitro model to evaluate the onset of rigor mortis. Measurements took place at ten points of time (t1-t10) beginning 103 min post mortem (pm). The mobility of the supraspinatus tendon was measured in Newton (N) with a modified sensor-enhanced arthroscopic grasper. (3) The mean load measured at the time point t1 was 28.0 ± 11.2 N. The first significant decrease of mobility occurred 151 min post mortem (t4) at a mean load of 30.2 ± 13.7 N. From 227 min pm to 317 min pm, there was no further significant increase. (4) Tendon mobility decreases significantly within the first three hours after the killing. Therefore, reliable results can be obtained within 150 min post mortem before the onset of rigor mortis alters the biomechanical properties.
Gesehen am 14.12.2022